Towards a state of the art and a conceptual framework of food sovereignty - Rivero Santos, Ana María (Universidad Distrital Francisco José de Caldas, 2017)
The purpose of this text is to provide a state of the art and a conceptual framework for food sovereignty, a concept that has its origin in the social movement and which nowadays is important in the academic debate in countries of the global North and South. After a contextualization of the emergence of the claim of food sovereignty, in the first part, the social movement of food sovereignty is described and recapitulated historically; from which it is provided a definition of food sovereignty with contributions from the peasant social movement, academy and international organizations. This is complemented by three analytical frameworks that contribute to the definition of food sovereignty: food regimes, the agro-food system and agroecology as the scientific domain of its study.